Analisis Faktor Determinan Penggunaan Sistem Aplikasi Pemeriksaan Laporan Keuangan dan Implikasinya - Erna Yuliasari (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2014)
Identifying the factors that affect the successful implementation of new software technology among users is very important for the success and failure of any system to operate in the new environment is highly dependent on user acceptance of the system. Badan Pemeriksa Keuangan Republik Indonesia (BPK) implement a new software supporting e-government to audit the financial statements of local governments , called Sistem Aplikasi Pemeriksaan Laporan Keuangan Pemerintah Daerah (SiAP LKPD) . This study aims to analyze the factorsmthat may affect the auditor in using SiAP LKPD and its implications on the performance of the auditor . Case studies conducted on BPK Representative West Java Province . The results of this study indicate that the characteristics of individuals with gender as a moderating variable , technological characteristics , and characteristics of the organizational context has an influence on behavioral intention to use SiAP LKPD. On the other hand , this study proves that age does not significantly moderate the impact of human factors on intention to use LKPD ready . Other results showed that the intention to use SiAP LKPD significantly affect user satisfaction and net benefits . User satisfaction also affects the net benefits . In addition, there is a relationship between human factors suitability, organization, and technology for the success of information systems.